A redemocratização e a (re)organização do PC do B na Paraíba (1979-1985): pelo direito à memória e a verdade como garantia a uma justiça de transição - Silva, Gregória Benário Lins e (2022)
Brazil is marked by serious violations of human rights during the military dictatorship period, established in April 1964 and lasting until March 1985. Thus, there were 21 years of crimes that afflicted humanity, and the country was even condemned by the Inter-American Court of Human Rights (IACHR) in two specific cases: the repression of the Guerrilla of Araguaia, which occurred between 1967 and 1974, considered by the Court to be a practice of genocide, and the murder of Vladimir Herzog, which took place in 1975. This work is aimed at purpose of discussing democratic openness in Brazil, seeking dialogue in the realization of fundamental rights, placing the State with full capacity to protect the individual and collective rights of citizens. The research is being developed from the bibliographic review, of works and authors that deal with the theme of the work, using the historical method, necessary above all to the study of the main types of rule of law. Homeland and foreign authors are essential to elucidate the fundamentals, such as Giuseppe Tosi (2014) and Marcelo Torely (2014), who maintain the importance of elucidating the serious violations of human rights, practiced by abuses of power in authoritarian regimes, with the purpose to create societies with the right as a way of promoting peace. The documentary analysis is present and verses on the documents of the National Information Service that are available on the website of the National Archives, as well as consultations on the documents of the PC do B, the Tribuna da Luta Operária magazine, resolutions, congresses, official newspapers of the time in Paraíba. In addition to the testimonies of the militants from 1975 to 1985, as an important part of data collection, for field research. Due to the pandemic, as well as the interviewees 'advanced age, the information used will be obtained through digital interviews based on the participants' reports. Predominantly the interpellation of the research is qualitative, in view of the need to deepen the documents that until recently were under secrecy, said to be confidential, with little-known and explored information.